A case of Fanconi anaemia in pregnancy. (December 2022) - Adeleke, Peter Akinlade; Ciantar, Etienne
Fanconi anaemia is a rare autosomal recessive chromosomal instability syndrome characterised by progressive bone marrow failure, skeletal defects, reduced fertility and increased susceptibility to malignancy. Successful pregnancy in both transplanted and non-transplanted patients have been recorded. In this paper, we present a woman diagnosed with Fanconi anaemia and who had a spontaneous conception at the age of 25 years with an uneventful delivery at 38 weeks of pregnancy.